Unleashing Employee Potential: Job Analysis, Workload Analysis, and Career Development as Key Drivers of Performance in Energy and Mineral Resources Office of West Java, Indonesia - Hayati, Tuti; Badruzaman, Jajang; Yusup Hanapia, Asep (The International Journal of Business Review (The Jobs Review), 2023)
The purpose of this study was to determine and analyze job analysis, workload analysis and career development on employee performance at the Department of Energy and Mineral Resources of West Java Province. As well as the influence of job analysis, workload analysis and career development on employee performance at the Department of Energy and Mineral Resources of West Java Province The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is the employee at the Department of Energy and Mineral Resources ofWest Java Province, with the sampling technique using the simple random sampling method. The data analysis technique used is path analysis. The results of this test prove that simultaneously and partially job analysis, workload analysis, career development and leadership style have a significant effect on employee performance at the Department of Energy and Mineral Resources of West Java Province